Analyzing the Vibration Exposure to the Safety and Health at Workplace: A Case in the Urea Granulation Unit of the Fertilizer Factory - Muhammad Taufiq; Iskandar Hasanuddin; Mohd Iqbal; Friesca Erwan (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2021)
This study aims to evaluate the vibration exposure experienced by workers in the Urea Granulation Screen Unit (UGSU) at the fertilizer factory in Aceh, Indonesia. This study involved 30 labors in charge as operators, mechanical maintenance officers, electrical maintenance officers, instrument maintenance officers, and inspectors. The measurement of vibration was carried out using a Triaxial Accelerometer with Integral Magnet and shows that the vibration exposure on the factory floor of the urea granulation screen unit occurs vertically with a minimum value of 0.298 m/s2 and a maximum of 1.630 m/s2. According to ISO 2631-1:1997, the maximum vibration values that occur are categorized as a likely health risk zone and result in uncomfortable reactions to the workers. Furthermore, this study analyzes the effect of vibrations on musculoskeletal problems using a Nordic Body Map (NBM) questionnaire. It reveals that the average score of musculoskeletal complaints is 71.6, which defines a high degree of pain. The results of the NBM questionnaire also showed that the vulnerable part of the body which experienced musculoskeletal complaints is the knee. The result of vibration exposure on this body part shows the highest value of 3.437 m/s2. To minimize occupational diseases and accidents, it is necessary to manage a working system that takes into account legal standards, ideal working time, and working shifts in the work area.